1998
DOI: 10.1016/s0167-8809(97)00094-7
|View full text |Cite
|
Sign up to set email alerts
|

Winter wheat cover cropping, VA mycorrhizal fungi and maize growth and yield

Abstract: The relationships among winter cover cropping, inoculum potential of vesicular-arbuscular mycorrhizal (VAM) fungi, and the growth and yield of a subsequent maize crop were investigated. In the first experiment, an autumn-sown winter wheat cover crop increased VAM fungal inoculum potential of a field soil as measured by an in situ maize bioassay during the following growing season. Infective extra-radical hyphal densities were significantly increased by cover cropping as interpreted from the effect of soil dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
39
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 26 publications
9
39
2
Order By: Relevance
“…We found that barley increased the number of spores by 42-72%, but vetch was similar to fallow. This result differs from Galvez et al (1995), who found that vetch had more spores number relative to fallow and from Boswell et al (1998), who did not report differences between CC and fallow. The heterogeneity in the results may be due to the methodology.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…We found that barley increased the number of spores by 42-72%, but vetch was similar to fallow. This result differs from Galvez et al (1995), who found that vetch had more spores number relative to fallow and from Boswell et al (1998), who did not report differences between CC and fallow. The heterogeneity in the results may be due to the methodology.…”
Section: Discussioncontrasting
confidence: 96%
“…Studies involving other main crops are scarce, but the effect of CC was similar, e.g., in leeks (Sorensen et al, 2005). In general, the percentages of increase relative to fallow in this study were moderate compared with other studies in which increments of 3-4-fold were found (Boswell et al, 1998;Kabir and Koide, 2002) or even 12-fold (Deguchi et al, 2007), probably because we found large values for root colonization even under fallow conditions. These large values may be related to the optimal temperature and soil moisture conditions from the beginning of maize growth.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations